Cryptococcus laurentii meningitis in a non-HIV patient. (2019) - Castro-Lainez, Miriams T.; Deliz-Aguirre, Rafael; Antunez, Daphne; Cruz-Codina, Marco; Cahuayme-Zuniga, Lizbeth; Vitale, Karla; Sierra-Hoffman, Miguel; Midturi, John K.
Abstract: Cryptococcus species (other than Cryptococcus neoformans) have been labeled as saprophytic and nonpathogenic in immunocompetent individuals in the past. In recent years, infections caused by non-neoformans Cryptococcus species have been recognized. Cryptococcus laurentii is known to be a rare human pathogen. In this case report, we present a 59-year-old man who did not have HIV infection with meningoencephalitis caused by Cryptococcus laurentii . No significant underlying immunosuppressive disorder was found. The only identifiable risk factors were that the patient was a farmer with previous exposure to pigeon droppings. Here, we describe what we believe to be the fifth reported case of meningitis caused by Cryptococcus laurentii .